2009
DOI: 10.1634/stemcells.2008-0734
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lmx1a in the Differentiation of Human Embryonic Stem Cells into Midbrain Dopamine Neurons in Culture and After Transplantation into a Parkinson's Disease Model

Abstract: Recent studies have provided important insight into the homeoprotein LIM homeobox transcription factor 1␣ (Lmx1a) and its role in the commitment of cells to a midbrain dopamine (mDA) fate in the developing mouse. We show here that Lmx1a also plays a pivotal role in the mDA differentiation of human embryonic stem (hES) cells. Thus, as indicated by small interfering RNA experiments, the transient early expression of Lmx1a is necessary for the coordinated expression of all other dopamine (DA)-specific phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 39 publications
6
69
0
Order By: Relevance
“…We confirmed the coexpression of FOXA2 and GIRK2 in SNc tissue that contains A9 dopaminergic neurons but not in the VTA, which contains A10 dopaminergic neurons. GIRK2/FOXA2 double-positive cells have not been induced from other stem cell sources using existing protocols (44)(45)(46), except for one that manipulates both the sonic hedgehog and WNT signaling pathways (43,47). Recent studies of fetal tissue engrafting in patients with PD or PD model rats have shown that A9 dopaminergic neurons are determinants of successful functional recovery (16,48) and decreased dyskinesia (49) and that they are associated with well-organized synaptic connectivity (16).…”
Section: Figurementioning
confidence: 99%
“…We confirmed the coexpression of FOXA2 and GIRK2 in SNc tissue that contains A9 dopaminergic neurons but not in the VTA, which contains A10 dopaminergic neurons. GIRK2/FOXA2 double-positive cells have not been induced from other stem cell sources using existing protocols (44)(45)(46), except for one that manipulates both the sonic hedgehog and WNT signaling pathways (43,47). Recent studies of fetal tissue engrafting in patients with PD or PD model rats have shown that A9 dopaminergic neurons are determinants of successful functional recovery (16,48) and decreased dyskinesia (49) and that they are associated with well-organized synaptic connectivity (16).…”
Section: Figurementioning
confidence: 99%
“…Brains sections were cut at 30 μm on a freezing microtome and processed for immunocytochemistry as described previously [6,14]. Antibodies were used as above except for the following differences: (β-tubulin III; 1:200), HNA (1:40); GFAP from Chemicon (1:200) and mouse monoclonal anti-CD11 from BD Biosciences (1:25).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…As described previously [14,18], 12 Fischer 344 rats (Taconic) were made Parkinsonian for these studies. Briefl y, rats were anesthetized with sodium pentobarbital [30 mg/kg, intraperitoneally (i.p.…”
Section: -Ohda Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the three neurodevelopmental factors (BAM) with factors known to be crucially involved in the embryonic development of mDA neurons as well as for their beneficial effect for DA differentiation of ESCs [63][64][65][66][67][68] seem to specifically boost the transdifferentiation towards DA-like neurons. Even though these findings provide a proof of principle for the amazing possibility to directly transdifferentiate/convert somatic cells just by simple forced expression of a specific set of transcription factors, also for iDA neurons a very thorough characterization would be necessary before one could seriously consider their clinical application.…”
Section: Towards a Direct Patient Specific Cell Replacement Strategymentioning
confidence: 99%